1967
DOI: 10.1001/archpsyc.1967.01730290009002
|View full text |Cite
|
Sign up to set email alerts
|

Long Lasting Effects of LSD on Normals

Abstract: This is a report of a study designed to measure personality, attitude, value, interest, and performance changes resulting from the administration of LSD to normals. Several investigators using LSD with humans in nontherapy experiments have observed that some of their subjects report various lasting effects attributable to the drug experience. 1 -2 In addition, the recent controversy over the nonmedical use of LSD has given rise to numerous claims and counterclaims in this regard. We have previously reported on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
1

Year Published

1971
1971
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 14 publications
3
47
1
Order By: Relevance
“…Trait anxiety is not expected to be altered by short-term psychotherapy (Spielberger et al, 1970), but a comparable finding was reported in recent research with psilocybin in cancer patients that reported significant reductions of trait anxiety (although without correction for multiplicity) but not state anxiety (Grob et al, 2011). Therefore, this trait change may be supported by neurobiological effects of adjunctive use of LSD, which was originally introduced for deepening and accelerating psychotherapeutic processing (Abramson, 1967) and, in some studies, was shown to alter personality traits (MacLean et al, 2011; McGlothlin et al, 1967; Savage et al, 1966). …”
Section: Discussionmentioning
confidence: 99%
“…Trait anxiety is not expected to be altered by short-term psychotherapy (Spielberger et al, 1970), but a comparable finding was reported in recent research with psilocybin in cancer patients that reported significant reductions of trait anxiety (although without correction for multiplicity) but not state anxiety (Grob et al, 2011). Therefore, this trait change may be supported by neurobiological effects of adjunctive use of LSD, which was originally introduced for deepening and accelerating psychotherapeutic processing (Abramson, 1967) and, in some studies, was shown to alter personality traits (MacLean et al, 2011; McGlothlin et al, 1967; Savage et al, 1966). …”
Section: Discussionmentioning
confidence: 99%
“…Very few controlled studies investigating the areas of psychological functioning affected by LSD, especially those areas espoused by proponents of consciousness-expanding experiences, have appeared. The work of McGlothlin et al (1967McGlothlin et al ( , 1968 represents the type of research with the greatest potential for generating scientific knowledge of the drug's effects.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the literature consists of case studies and statistical surveys which could easily be criticized on methodological grounds. There are a few unusually clean and well-planned studies (Ditman, Tietz, Prince, Forgy, & Moss, 1967;McGlothlin, Cohen, & McGlothlin, 1967Savage, Fadiman, Mogar, & Allen, 1966;Shagass & Bittle, 1967) but these are exceptional.…”
mentioning
confidence: 99%
“…In early trials of hallucinogens administered under supportive conditions, 50 - 80% of participants claimed lasting beneficial changes in personality, values, attitudes and behavior (Metzner and Editors, 1963; McGlothlin and Arnold, 1971). Some of the most frequent subjective reports included greater appreciation of music, art and nature, greater tolerance of others, and increased creativity and imagination (McGlothlin et al, 1967). Consistent with these findings, Studerus et al (2010) recently reported that nearly 40% of participants in several laboratory studies of psilocybin claimed positive long-term changes in aesthetic experience and in their relationship with the environment (i.e., nature) following their psilocybin sessions.…”
mentioning
confidence: 99%